Anti-bacterial efficacy via drug-delivery system from layer-by-layer coating for percutaneous dental implant components - de Avila, Erica D. [UNESP] (2019)
Percutaneous medical devices are prone to bacterial contamination that causes dramatic clinical conditions. At the percutaneous level of dental implant systems, microbial pathogens induce biofilm formation that may result in bone resorption and dental implant loss. In view of peri-implantitis caused by bacterial inflammation at the percutaneous abutment region, we here establish a novel drug release system based on layer-by-layer (LbL)-deposited poly(acrylic acid) (PAA) and poly-L-lysine (PLL) coatings on titanium (Ti). Detailed multilayer coating characterization was performed by different microscopy and spectroscopy techniques to probe physical and chemical properties. Our data revealed a significant difference in roughness average between ten double layers coated (141 nm ±30) and uncoated Ti discs (115 nm ±40). Although roughness of the coatings increased significantly after immersion in water for 24 h at 37 °C, this physical property remained below 200 nm. Coating stability was confirmed under neutral and acidic pH, mimicking healthy and diseased/inflammatory environments, respectively. LbL coatings supported in vitro human keratinocytes growth, demonstrating absence of cytotoxic effects. Tetracycline (TC) showed an initial burst release under neutral and acidic conditions, which further demonstrated robust antibacterial efficacy against Porphyromonas gingivalis. However, a convenient pH-dependent 2-folds increase in TC release was observed for coatings incubated at pH = 4.5. Sustained TC release was observed from coatings up till 15 days of incubation in both pH conditions. These results demonstrate the potential application of this simple surface modification to leverage anti-bacterial efficacy at the percutaneous abutment region.